Rabbani Education: Basic Concepts, Design and Implications of Rabbani Education Learning - Anam, Nurul; Fikroni, Moh. Rofid (Tribakti: Jurnal Pemikiran Keislaman, 2020)
Rabbani education is a basic concept to overcome various problems in human life. This concept is understood as a process that actively develops human potentials through the process of purification, instilling and incarnation into a generation of rabbani. From this understanding, there are three core processes of rabbani education, namely the process of purification, instilling, and incarnation. The design of rabbani education learning is centered within Al-Qur'an Surah Al-Alaq verses 1-5. This surah is the first revelation revealed to the Prophet Muhammad. Not only this revelation signifies that the prophet as an Apostle or messenger, but also as a student who was educated by God and became an educator for all humanity. This first revelation contains the core theory of learning design. Therefore, the basic concept and design of rabbani education learning has several implications that can be actualized in the context of Islamic education in this century, namely: 1) rabbani education empties and ends at the peak of a life mission, which is divinity or monotheism; and 2) rabbani education that had been through by the Prophet Muhammad is a reflection of the ideality of an Islamic education process.